Integrated photonic devices for realizing photonic quantum computing: part 3 - Xu, JiaJun (Nanyang Technological University, 2024)
The main goal of this research project is to maximize light output concentration through voltage alignment by characterizing and optimizing Optical Phased Array (OPA) LiDAR chips. The research includes an extensive experimental design that includes Fourier Plane image acquisition, voltage modification processes, and image analysis afterward. The obtained results show a clear difference between the uncalibrated and calibrated states: scattered images in the former case indicate phase misalignment, while coherent single-dot images in the later case demonstrate successful calibration. Additional understanding is obtained by investigating the best voltage choice among several peaks at kx=0.0, clarifying the complex interaction between heating effects and voltage sensitivity in thermal phase tuners. Future research directions include investigating more sophisticated calibration algorithms, integrating temperature compensation mechanisms, refining voltage calibration techniques, validating results through real-world testing scenarios, and encouraging ongoing research and cooperation within the LiDAR community. All things considered, this work advances our knowledge of and ability to use OPA LiDAR technology, opening the door to more accurate and dependable optical sensing systems in a variety of applications.